The Guardian Council of Iran (1980-2022): Social and Professional Recruitment Factors - Vaskin, Ilya (Journal of Economic Sociology, 2025)
The article analyzes the socio-demographic composition of the secular jurists and faqihs of the Iranian Guardian Council. The Guardian Council is a hybrid institution that performs the functions of an upper chamber of parliament, a constitutional court, and an electoral committee. The research employs a structural-demographic method. The research dataset consists of seven Guardian Councils, from 1980 to 2022, with 51 members and 123 appointments. The results of the study show that there are structural differences between secular jurists and fuqaha. Secular jurists are, on average, younger than fuqaha in terms of both minimum and maximum age. Fuqaha primarily study in seminaries, while secular lawyers attend universities and also receive degrees in France and Britain. Secular lawyers are not professionally homogeneous; among them are former employees of the courts, the prosecutor’s office, the state civil service, lawyers, and academics. The regional origins of secular jurists and fuqaha also differ significantly; they share only one unifying province, Isfahan, which may be due to the significant role of patrimonial ties in the recruitment of elites. Overall, this difference indicates the presence of two legal cultures: secular and Islamic, which are reflected in different socio-demographic patterns in recruiting members of the Guardian Council. The professionalization and socialization of these groups greatly influence their decision-making in various forms of social life, including the legislative branch to which the Guardian Council belongs. However, this study is limited to the secular jurists and fuqaha of the Council.